Analysis of the National Health Expenditure Survey Round 1 and Design of Survey Protocol for NHES Round 2 (Phase 1) - Ida Marie T. Pantig; Lovely Ann C. Tolin; Xylee Javier; Valerie Gilbert Ulep (Philippine Institute for Development Studies (PIDS), 2023)
The universal health care (UHC) law mandates that all Filipinos should have access to essential primary care services with a focus on preventive healthcare. As plans are being made by the government to map out a comprehensive outpatient benefit package covering primary care, it would be a worthy exercise to explore the different outpatient use patterns of the population even as PhilHealth rolled out various primary care benefit packages in the past decade. In the absence of a sound primary healthcare system in the Philippines, Filipinos may have identified with a usual healthcare provider that they seek during a health need. A usual healthcare provider is defined in this study as a particular doctor's office, clinic, health center, or other place that the household member usually goes to when sick or needs advice about his/her health. As the PhilHealth expands its outpatient benefit package as part of the transition to UHC, the different trends in outpatient care utilization would be worth exploring since having a usual healthcare provider may affect utilization patterns across the continuum of care. The first round of the National Health Expenditure Survey (NHES) was conducted in 2018 and the survey covers areas such as healthcare service utilization and charges, types of facilities visited, health insurance coverage and sources of health financing, among others. Using this dataset, we explore how having a usual healthcare provider can be a determinant of healthcare service use. Specifically, this study examines the differences in outpatient care utilization among those with and without usual care providers. Specifically, the objectives of this study are: (1) to explore health service use trends in outpatient care services, (2) to explore the determinants of having a usual healthcare provider, and (3) to examine whether having a usual healthcare provider affects outpatient care, inpatient admissions, and emergency room visits. Using descriptive analysis and measures of association, we find that in general, more households with usual healthcare providers utilize outpatient care services compared to those with none. In addition, the individuals' age, household head's age, insurance coverage status, urbanity and wealth quintile are determinants of having a usual healthcare provider, while household size, sex, household head's education and Pantawid membership do not significantly determine if an individual having one. Lastly, we find that having a usual health provider increases the probability of seeking outpatient care services, inpatient admissions, and emergency room visits.
Keywords: 330; health utilization; usual healthcare provider; primary care; preventive care; outpatient care; hospitalization